Antiproliferative Properties Of Clitoria Ternatea And Vitex Negundo On Cancer Cell Lines - Dashti, Neda Ganjali (2013)
Leaves and flowers of Clitoria ternatea and Vitex negundo were evaluated by proximate analysis using the AOAC method. The mineral and heavy metal contents in both plants were determined using the Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES). The major aim of this study was to examine the anti-proliferative activities (IC50 value <100 μg/mL) of water and methanol extracts of both plants against human cancer origin cell lines, namely MCF-7 (hormone-dependent breast cancer cell line), MDA-MB-231 (non-hormone-dependent breast cancer cell line), Caov-3 (human ovary cancer cell line), Hela (human cervical cancer cell line), HepG2 (human liver cancer cell line) and Hs27 (human non-cancer-origin fibroblast cell line). The cell growth inhibition was evaluated by the 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay for 24, 48 and 72 hours. Results from the proximate analysis indicated that the leaves and flowers of Vitex negundo and Clitoria ternatea were composed of fiber (2.1% to 11.6%), carbohydrate (2.2% to 18.9%), protein (0.32 to 0.87%), fat (2.5% to 7%), ash (0.45% to 8%) and moisture (53.4% to 92.4%), respectively. Leaves and flowers of Vitex negundo were rich in calcium (10.5 and 5.5 mg/g), respectively. All the analysis of heavy metals (Ni, Cd, As, Pb) were found to be at a lower concentration and were below the detection limits, thus making the plants safer for consumption.